Determine the Forage Importance Value of Dhaher Al Khribat forest (Latakia – Syria) - Mohamed, Yassin Chikh (Latakia University Journal -Biological Sciences Series, 2020)
This research had been implemented in Daher Al Kheribat forest in Jableh territory. The Field surveys had been carried out in the mid - april 2016. There were 47 plant species recorded, wich were distributed in 40 genus and 19 families. The most common family was Poaceae. Bromus tectorum L. and Alopecurus utriculatus Banks & Sol. (of forage significance) obtained the highest values of relative importance (29,56 % on the second place, 17.96 % on the first place respectively) and Euphorbia helioscopia L. (of forage insignificance) (5.97 % on the second place). The number of plant species, present in all investigated samples, was limited to 9 species. However, the three species had the highest vegetation coverage (59 %, 41%, 14.66 % respectively). Results were showed that ΣRIV were 83.07% on the first place, 82.88% on the second place, 84.78% on the third place and 83.58% as a general rule on the studied area. There for we can conclude, that the study area is generally suitable for grazing and that the area has a forage importance. نُفِّذَ البحث في غابة ضهر الخريبات في منطقة جبلة، وأجريت المسوح الحقلية في منتصف نيسان سنة 2016. سجل وجود47 نوعا، توزعت على40 جنسا و19 فصيلة. وأنواع الفصيلة الكلئية Poaceae هي الأكثر انتشارا. أبدى الشويعرة Bromus tectorum L. وذنب الثعلب المنتفخ Alopecurus utriculatus Banks & Sol.، ذات الأهمية الرعوية، أعلى قيمتين للأهمية النسبية، (29.56% في الموقع الثاني، 17.96% في الأول على التسلسل)، والحليبة Euphorbia helioscopia L. (5.97% في الموقع الثاني)، وهو عديم الأهمية الرعوية. ولقد اقتصر عدد الأنواع النباتية المتواجدة في جميع العينات المدروسة على 9 أنواع، لكن الأنواع الثلاثة تلك سجلت أعلى تغطية نباتية (59% ، 41% ، 14.66% على التوالي). أظهرت النتائج أن مجموع الأهمية النسبية للأنواع ذات الأهمية الرعوية RIV∑ في الموقع الأول بلغ 83.07%، وفي الثاني 88.82%، وفي الثالث 84.78%، وفي منطقة الدراسة بشكل عام83.58%، وهكذا نخلص إلى القول بأن منطقة الدراسة صالحة للرعي بشكل عام، وتتمتع بدرجة أهمية رعوية جيدة.